Identifikasi Kandungan Kimia Golongan Senyawa Daun Pohon Kapuk (Ceiba Pentandra L.) Sebagai Obat Tradisional - Suaibatul Aslamiah; Haryadi Haryadi (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2014)
Kapok tree is used as an antidote for post-birth mother and for the treatment of deep wounds. Based benefit cottonwood tree researchers interested in knowing the content of the active compounds in the leaves of cottonwood with an experimental method for identifying active compounds. The method used is an experiment to identify active compounds what is contained in the leaves of cottonwood trees. Research conducted at the Faculty of Health Sciences at the University of Muhammadiyah Palangkaraya assay ethanol -soluble extract the same method as the determination of water content i.e. gravimetric method. The solvent used is 95 % ethanol, and then evaporated. Methods used in the determination of cider levels equal to the determination of levels of sari that is soluble in water that is a method of gravimetric. The solvent used for the solution penyari i.e. 95% ethanol is then evaporated over a water bath until dry and heated in an oven with a temperature of 1050 C to constant weight. Levels of ethanol -soluble extract obtained results, namely 4.8 % Test results can Fitokomia in tannin (fe Cltambah egg albumin) negative, positive drgendroff alkoloid, Alkaloids meyer negative, negative Alkoloid Bouchardat, saponin HHCL2N positive, negative Flavonoides and steroids and Terp Steroid and Terpenoid (acetate acid concentrated sulfuric acid anhidtrat positive.